2004
DOI: 10.1002/chin.200406106
|View full text |Cite
|
Sign up to set email alerts
|

New Styryl Sulfones as Anticancer Agents.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Surgical video data from publicly available sites are being used for training models, but the quality of these video sources is variable. A recent consensus statement 4 suggested that a 10-year time hori-zon is likely for real-time implementation of these algorithms, and retrospective training tools may be available in the next 2 years. Appreciating the nascent nature of surgical vision will allow it to develop as a collaboration that will ensure that tools work in concert with surgeons and ultimately transform surgical care.…”
Section: Computer Visionmentioning
confidence: 99%
“…Surgical video data from publicly available sites are being used for training models, but the quality of these video sources is variable. A recent consensus statement 4 suggested that a 10-year time hori-zon is likely for real-time implementation of these algorithms, and retrospective training tools may be available in the next 2 years. Appreciating the nascent nature of surgical vision will allow it to develop as a collaboration that will ensure that tools work in concert with surgeons and ultimately transform surgical care.…”
Section: Computer Visionmentioning
confidence: 99%
“…Among the compounds synthesized, 6-chloro-1H-(benzo [d]imidazol-2-yl) methyl [(E)-2-(4-chloro-3-methyl phenyl)-1-ethenyl] sulphone, 2, has shown 51% tumour growth inhibition in mice implanted with HT-29 human carcinoma at 400 mg/kg orally (Vedula et al, 2003).…”
Section: Benzimidazoles As Anticancer Agentsmentioning
confidence: 99%